Enhancing Students Proficiency in English Grammar Through the Implementation of Snowball Throwing Pedagogical Model - Arsai, Alfons Napoleon; Arsai, Almendita Flora W. (Journal of English Culture, Language, Literature and Education, 2023)
This research endeavors to assess students proficiency in English grammar pertaining to the past tense through a comparative analysis of their pre test and post test scores Employing the innovative snowball throwing learning model as the intervention strategy this study aims to augment students grammatical competence in the past tense The research methodology adopts a classroom action research approach conducted across two cycles The subjects comprise Grade X students in the secretary class of the first state Vocational school in Manokwari selected through purposive sampling from four classes Research instruments include a reading test observation sheet and lesson plan The initial data analysis of the pre test yields a result of 29 2 indicating a classification in the poor category However following the implementation of the snowball throwing model through two cycles treatment one and treatment two noteworthy improvement is observed Treatment one yields a result of 60 3 in the fair category while treatment two results in an average score of 80 2 classifying as Good Importantly this score serves as the post test score The findings underscore the efficacy of the snowball throwing model in enhancing students grasp of past tense grammar< p>